History of St. Paul's Church - Swett, Ruth Ellen; Patrick, William E.; Sweitzer, Matilda L.; Gardette, M.D.; Bender, Cora; Scott, Henry
Typed manuscript documenting the history of St. Paul's Episcopal Church up to January 1936.